The Financial Support Structure of Small and Medium – Scale Enterprises (SMEs) In Ghana: A Comparative Study of Capital Market Finance and Bank Finance. - Aidoo,, Jacob Benson (2018)
The introduction of capital market in Ghana with the establishment of the Ghana Stock Exchange (GSE) in 1989 was received as an initiative that provides an alternative avenue for businesses to raise long term capital to finance their operations and list on the exchange. The Government was also expected to divest its interest in the over 300 state-owned enterprises (SOEs) at the time through the GSE to boost activity on the stock market. After 25 years of capital market operation, a large number of medium and large scale companies still operate outside the formal capital market and mostly depend on bank finance in spite of limited access to credit which has been identified as critical factor constraining business growth in Ghana. The low utilization of capital market finance has implication for the number of companies listed on the GSE. With 11 companies listed in 1990, the number increased to 37 in 2016, giving an average of one listed company per year. To this end, the main purpose of the present study was to explore factors that influence the decision of companies to raise funds from the capital market for their operations. The study relied mainly on primary data, and structured questionnaires employed as data collection instrument. Simple random sampling technique was adopted to select 400 respondents and binary logistic regression used as the estimation technique. The results show a positive and significant relationship between loss of control, credit availability, knowledge about capital market, and capital market finance. It also revealed a negative and significant relationship between growth stage of the firm and capital market finance. The results further show that SMEs are over dependent on bank finance due to the constraint they face in accessing other forms of external finance. Based on the results, the study recommends intensive education and awareness creation programmes for potential issuers on the benefits of capital market finance.